A literature review of the healthcare resource use and productivity burden of X-linked hypophosphataemia - Rafael Pinedo-Villanueva; Muhammad K. Javaid; Angela Williams; Isabelle Whittle; Matilde Franceschini; Ben Johnson (Frontiers in Health Services)
IntroductionX-linked hypophosphataemia (XLH) is a rare, genetic, renal phosphate wasting disorder that causes a lifelong rapid progression of morbidities, which are associated with substantial humanistic and economic burden. A structured literature review was carried out to identify publications reporting healthcare resource use and productivity impact of XLH to provide a comprehensive description of the burden.MethodsLiterature searches of the Embase®, Medline®, and EconLit electronic databases were carried out in August 2022 using free-text and subject heading search terms regarding XLH-related clinical morbidities and associated healthcare resource use, limited to English language records from 1992 onwards.ResultsAfter screening by pre-specified inclusion/exclusion criteria, 22 publications were selected for inclusion in the review. Use of conventional pharmacological therapy with oral phosphate and/or active vitamin D was reported in 15 publications, in up to 100% of paediatric patients and 75% of adults. Findings indicated that a high proportion of patients with XLH undergo orthopaedic procedures/surgeries, including a history of osteotomy in up to 25% of paediatric patients and 61% of adults, and a history of growth plate stapling in up to 63% of paediatric patients and 20% of adults. A high prevalence of fractures (in up to 61% of adults) and use of assistive mobility devices was also reported. The findings highlighted a substantial prevalence of morbidities, either due to persistently low phosphate levels or complications of conventional therapy, that had directly associated healthcare resource use, including dental problems, hearing problems, hyperparathyroidism, and nephrocalcinosis. Healthcare resource use and associated clinical events were generally found to be higher in adults compared with paediatric patients, which is consistent with the natural history of XLH as a progressive lifelong condition. Studies also highlighted the negative impact of XLH on school attendance and the ability to work.DiscussionThe results of this structured literature review emphasise the lifelong impact of XLH, showing that it is associated with a substantial economic burden, across many healthcare resource use categories including pharmacological therapy, management of pain and mobility, orthopaedic procedures, morbidities due to XLH or conventional therapy, and work/school productivity.